GOOD SCHOOL GOVERNANCE: DAPATKAH SISTEM INFORMASI PENGADAAN DI SEKOLAH MEMODERASI DETERMINAN PERFORMANCE BUDGETING? - Pituringsih, Endar; Basuki, Prayitno; Handajani, Lilik (Jurnal Aplikasi Akuntansi, 2025)
In this study, we will examine the following relationship: that between Performance Budgeting and Good School Governance, that between Performance Budgeting and the organizational culture management system, and that between Performance Budgeting and the management control system and organizational culture, as moderated by SIPLah. A total of 204 high schools on Lombok Island participated in this study. Using a combination of the Slovin formula and a purposive sampling technique, 201 respondents from 67 high schools made up this research sample. With the Aid of Smart PLS Version 4.0, The Research Data was subsequently analyzed using PLS-SEM. This Study's Findings Suggest That High School Budgeting Performance Can Be Positively Affected by Management Control Systems and Organizational Culture and That Use of SIPLah Does Not Diminish This Effect. According to this study's findings, Performance Budgeting Also Positively Affects Good School Governance. This means high schools on Lombok Island can achieve better school governance by enhancing their management control systems and cultivating a positive organizational culture, leading to better budgeting performance.